Alcohol Amination Catalyzed by Copper Powder as a Self‐Supported Catalyst. Issue 13 (26th November 2018) - Wu, Yajuan; Huang, Yongji; Dai, Xingchao; Shi, Feng
Abstract: Catalytic alcohol amination is a sustainable reaction for N ‐alkyl amine synthesis. Homogeneous and supported copper catalysts have long been studied for this reaction and have given some impressive results. In this study, copper powder is found to behave as an active catalyst for alcohol amination, giving better catalytic performance than metal‐oxide‐supported nanocopper catalysts. Catalyst characterization suggests that the copper powder can be considered as a self‐supported nanocopper catalyst (i.e., nanocopper supported on copper particles). These results might promote the study of unsupported transition metal powders in sustainable catalytic reactions. Abstract : The powder and the glory : Catalytic alcohol amination is a sustainable reaction for N ‐alkyl amine synthesis. In this work, a self‐supported copper powder catalyst was designed and prepared for alcohol amination. Its catalytic performance was much better than the oxide‐supported nanocopper catalysts. This concept may lead to new opportunities for metal‐ or porous metal‐supported metal catalysis.